COMMUNICATION SKILLS-BASED NEED ANALYSIS ON THE TEACHING AND LEARNING OF MARITIME ENGLISH FOR VOCATIONAL SCHOOL - Hellystia, Devi; Budiwaty, Suci (Journal of Language and Literature, 2023)
This research attempts to find out the students’ perception regarding communication skills in English for Maritime. The research was carried out at a vocational school in SMK 04 Pandeglang, West Java. The data were taken from questionnaires, interviews, and observed exams. It was qualitative research where the data are communicated and described narratively. According to the findings, students' communication skills in Maritime English were categorized as poor. The main reason for their poor performance was the current book did not take into account the students' EFL communication skills in the field of Maritime. A comprehensive material that focused on communication skills in the field of Maritime was considered essential. The students generally agreed that the four language skills in Maritime English which comprise listening, speaking, reading, and writing were essential for their work in the future. However, they prioritized writing and speaking skills as the most crucial ones. The conclusion showed that it should be considered teaching improvement and learning materials development which encourage students to improve their English communication skills in the field of Maritime.